Diffuse parenchymal lung disease as first clinical manifestation of GATA-2 deficiency in childhood - Svobodova, Tamara; Mejstrikova, Ester; Salzer, Ulrich; Sukova, Martina; Hubacek, Petr; Matej, Radoslav; Vasakova, Martina; Hornofova, Ludmila; Dvorakova, Marcela; Fronkova, Eva; Votava, Felix; Freiberger, Tomas; et al. (BMC pulmonary medicine, 2015)
BACKGROUND: GATA-2 transcription factor deficiency has recently been described in patients with a propensity towards myeloid malignancy associated with other highly variable phenotypic features: chronic leukocytopenias (dendritic cell-, monocyto-, granulocyto-, lymphocytopenia), increased susceptibility to infections, lymphatic vasculature abnormalities, and sensorineural deafness. Patients often suffer from opportunistic respiratory infections; chronic pulmonary changes have been found in advanced disease. CASE PRESENTATION: We present a case of a 17-year-old previously healthy Caucasian male who was admitted to the hospital with fever, malaise, headache, cough and dyspnea. A chest X-ray revealed bilateral interstitial infiltrates and pneumonia was diagnosed. Despite prompt clinical improvement under antibiotic therapy, interstitial changes remained stable. A high resolution computer tomography showed severe diffuse parenchymal lung disease, while the patient's pulmonary function tests were normal and he was asymptomatic. Lung tissue biopsy revealed chronic reparative and resorptive reaction with organizing vasculitis. At the time of the initial presentation to the hospital, serological signs of acute infection with Epstein-Barr virus (EBV) were present; EBV viremia with atypical serological response persisted during two-year follow up. No other infectious agents were found. Marked monocytopenia combined with B-cell lymphopenia led to a suspicion of GATA-2 deficiency. Diagnosis was confirmed by detection of the previously published heterozygous mutation in GATA2 (c.1081 C > T, p.R361C). The patient's brother and father were both carriers of the same genetic defect. The brother had no clinically relevant ailments despite leukocyte changes similar to the index patient. The father suffered from spondylarthritis, and apart from B-cell lymphopenia, no other changes within the leukocyte pool were seen. CONCLUSION: We conclude that a diagnosis of GATA-2 deficiency should be considered in all patients with diffuse parenchymal lung disease presenting together with leukocytopenia, namely monocyto-, dendritic cell- and B-lymphopenia, irrespective of severity of the clinical phenotype. Genetic counseling and screening for GATA2 mutations within the patient's family should be provided as the phenotype is highly variable and carriers without apparent immunodeficiency are still in danger of developing myeloid malignancy. A prompt recognition of this rare condition helps to direct clinical treatment strategies and follow-up procedures.
Keywords: mladiství; Radiography; Lymphopenia; lymfopenie; mužské pohlaví; mutace; Lung Diseases, Interstitial; Monocytes; monocyty; B-lymfocyty; intersticiální plicní nemoci; GATA2 Transcription Factor; vaskulitida; leukopenie; radiografie; plíce; B-Lymphocytes; Humans; Mutation; transkripční faktor GATA2; Epstein-Barr Virus Infections; infekce virem Epsteina-Barrové; syndrom; Leukopenia; Adolescent; Lung; Syndrome; lidé; Male; Vasculitis